Study on hsa_circ_101209 in Plasma of Pregnant Women with Deep Venous Thrombosis - Zhang Y; Li J (International Journal of General Medicine)
Yuhong Zhang, Jun Li Center for Obstetrics and Reproductive Medicine, The Affiliated Hospital of Yunnan University, Kunming City, Yunnan Province, 650032, People’s Republic of ChinaCorrespondence: Jun Li, Center for Obstetrics and Reproductive Medicine, The Affiliated Hospital of Yunnan University, No. 176, Qingnian Road, Kunming, Yunnan, 650032, People’s Republic of China, Email lijun1152061295@hotmail.comBackground: This study analyzed the expression and diagnostic value of hsa_circ_101209 in plasma of pregnant women with in deep vein thrombosis (DVT).Methods: By circRNA microarray detection and GO/KEGG analysis, hsa_circ_14797 targeting miRNA-mRNA network was predicted. Sixty women with DVT were selected as the DVT group, and 60 women without DVT as the non-DVT group. hsa_circ_14797 in plasma was detected, as well as D-dimer (D-D) concentration and P-selectin expression. Target genes that may be regulated by hsa_circ_14797 were predicted, and GO analysis and KEGG pathway enrichment analysis were performed.Results: hsa_circ_14797 was highly expressed in DVT. hsa_circ_14797 in plasma of DVT patients was positively correlated with D-D (r = 0.358, P = 0.001). The AUC of plasma hsa_circ_14797, D-D, and P-selectin for maternal DVT diagnosis were 0.787 (95% CI: 0.710– 0.864), 0.882 (95% CI: 0.821– 0.943), and 0.825 (95% CI: 0.754– 0.895), respectively. The AUC of hsa_circ_14797 combined with D-D was 0.886 (95% CI: 0.828– 0.944). The AUC of hsa_circ_14797 combined with P-selectin was 0.904 (95% CI: 0.853– 0.954). The AUC of P-selectin combined with D-D was 0.935 (95% CI: 0.893– 0.978). The AUC of hsa_circ_14797 combined with D-D and P-selectin was 0.953 (95% CI: 0.920– 0.986). The functions of hsa_circ_14797 included the biological processes of angiogenesis, vascular development, and vascular morphology. The enrichment pathways included PI3K-Akt pathway, TGF-β pathway, and cytokine-cytokine receptor interaction.Conclusion: hsa_circ_14797, D-D, and P-selectin in plasma of DVT pregnant patients are increased, and hsa_circ_14797 in plasma is positively correlated with D-D. hsa_circ_14797 combined with D-D and P-selectin can improve the accuracy of diagnosis of DVT and contribute to the early diagnosis of DVT.Keywords: Deep vein thrombosis, circRNA, D-dimer, P-selectin, Biomarkers